OPTIMALISASI ONE STOP SERVICE PUSAT PEMBELAJARAN KELUARGA BALAI RW DI LINGKUNGAN KELURAHAN KUTISARI - Mutiara Bahar; Kalvin Edo Wahyudi (Journal Publicuho, 2024)
Violence that often occurs in the family environment today requires special attention, families who should play an important role in meeting the needs of their children are also undeniably experiencing many failures in it. To prevent acts of violence and improve the quality of family life, prevention must be pursued together, with this the Surabaya City Government is committed to collaborating with DP3APPKB Surabaya City to carry out a prevention effort program, one of which is through the Surabaya City Puspaga which is now expanded to the lower layers of society, namely the RW Hall Puspaga. This research uses a qualitative descriptive approach. The data collection techniques used are through direct observation (observation), interviews, documentation. The theory used is optimization theory with 3 (three) indicators belonging to Hotniar Siringoringo, namely goals, alternative decisions, and limiting resources. The results showed that the Optimization of One Stop Service Puspaga (Family Learning Center) Balai RW in Kutisari Village was quite optimal, but there were still limiting resources including professional staff who performed services and the infrastructure used.